KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR MENURUT TEORI POLYA - Ruqoiyyah, Siti; Muammar; Wilujeng, Hestu (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
This research aims to analyze elementary school students' mathematical problem-solving abilities according to Polya Theory. This research combines the Concurrent Triangulation type, which combines qualitative and quantitative research methods simultaneously, both in data collection and analysis. Data was collected using tests, interviews and documentation. The subjects of this research were 25 grade IV students at MI Qubbataul Islam. Quantitative data was analyzed using quantitative descriptive, and qualitative data was analyzed using the Miles and Huberman interactive model. Test the validity of quantitative data, test students' mathematical problem-solving abilities using the Product Moment Correlation validity test and test reliability using Cronbach's Alpha. Qualitative data validity techniques were tested using triangulation and reference adequacy. The research results show that students' mathematical problem-solving abilities are still in the medium category, with 8% having mathematical problem-solving skills in the high class, 80% in the medium category, and 12% in the low sort.